2004
DOI: 10.1074/jbc.m406392200
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast Differentiation Is Impaired in the Absence of Inhibitor of κB Kinase α

Abstract: Signaling through the receptor activator of nuclear factor B (RANK) is required for both osteoclast differentiation and mammary gland development, yet the extent to which RANK utilizes similar signaling pathways in these tissues remains unclear. Mice expressing a kinase-inactive form of the inhibitor of B kinase ␣ (IKK␣) have mammary gland defects similar to those of RANKnull mice yet have apparently normal osteoclast function. Because mice that completely lack IKK␣ have severe skin and skeletal defects that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 40 publications
7
76
0
Order By: Relevance
“…We looked at genes upregulated in response to RANKL during osteoclastogenesis (identified in Chaisson et al [6]), and studied the regulation of a subset of these genes in PC3 cells. Using RT-PCR we confirmed that MMP-9 was upregulated approximately 25-fold in PC3 cells at 12 hr post-RANKL stimulation (Fig.…”
Section: Rank Signaling Results In Changes In Global Gene Expression mentioning
confidence: 99%
“…We looked at genes upregulated in response to RANKL during osteoclastogenesis (identified in Chaisson et al [6]), and studied the regulation of a subset of these genes in PC3 cells. Using RT-PCR we confirmed that MMP-9 was upregulated approximately 25-fold in PC3 cells at 12 hr post-RANKL stimulation (Fig.…”
Section: Rank Signaling Results In Changes In Global Gene Expression mentioning
confidence: 99%
“…These results, together with the result of the NIK studies, indicate that the NIK/IKK1 pathway is not involved in basal osteoclastogenesis, but is important for stimulated differentiation such as during inflammation or cancer. 18 The importance of IKK1 in in vitro differentiation of osteoclasts and in p100 processing to p52 upon RANKL stimulation has been confirmed using bone marrow cells expressing a kinase-dead IKK1. 19 However, this study did not confirm the in vivo role of IKK1.…”
Section: Nf-jb and Osteoclast Differentiationmentioning
confidence: 94%
“…In vitro experiments using IKK1-deficient fetal liver cells demonstrated the involvement of IKK1 in RANKL-mediated osteoclastogenesis. 18 Chaisson et al described a normal number of TRAP þ osteoclasts, but also showed a decrease in the number of multinucleated cells. Processing of p100 into p52 was also impaired after RANKL treatment.…”
Section: Nf-jb and Osteoclast Differentiationmentioning
confidence: 98%
“…TNF can also induce the expression of c-fos and NFATc1, in a p50/p52-dependent manner, albeit at lower levels than RANKL [34], indicating a pro-differentiation role for TNFα as well. Furthermore, addition of TNFα with RANKL significantly rescues the ability of NIK-or IKKα-deficient precursors to form OCs in vitro, despite the fact that p100 levels are elevated [12,23,35], suggesting that the differentiation signal is independent of alternative NF-κB activation. However, in vivo, the osteoclastogenic response of relB −/− mice was limited in response to TNFα [22].…”
Section: Tnfα Effects In the Ocmentioning
confidence: 99%
“…NIK −/− mice have a mild but significant increase in trabecular bone volume at baseline, but have a severely blunted OC response to RANKL administration in vivo [21,22]. In the absence of NIK or IKKα, p100 cannot be processed to p52, and accumulated p100 acts as a global IκB over time [23]. Thus, in such cases although RANKL-naïve BMMs have normal IκBα degradation and p65 activation acutely, preOCs differentiated in RANKL for 48 hours do not have significant levels of p65, p50, RelB or p52 in the nucleus.…”
Section: Rankl-induced Nf-κbmentioning
confidence: 99%